Conjugated Amplifying Polymers for Optical Sensing Applications - Rochat, Sébastien; Swager, Timothy M (ACS applied materials & interfaces, 2013)
Thanks to their unique optical and electrochemical properties, conjugated polymers have attracted considerable attention over the last two decades and resulted in numerous technological innovations. In particular, their implementation in sensing schemes and devices was widely investigated and produced a multitude of sensory systems and transduction mechanisms. Conjugated polymers possess numerous attractive features that make them particularly suitable for a broad variety of sensing tasks. They display sensory signal amplification (compared to their small-molecule counterparts) and their structures can easily be tailored to adjust solubility, absorption/emission wavelengths, energy offsets for excited state electron transfer, and/or for use in solution or in the solid state. This versatility has made conjugated polymers a fluorescence sensory platform of choice in the recent years. In this review, we highlight a variety of conjugated polymer-based sensory mechanisms together with selected examples from the recent literature.